Ecological systems theory : (re)constructing identity in Toni Morrison's beloved - Donelli, Iva (Array, 2020)
In this paper, Toni Morrison’s novel Beloved (1987) will be considered from the point of view of developmental psychology. Morrison’s works can be seen as representing an intertwinement of social, historico-political and emotional themes which play a crucial role in the identity construction of the author’s characters. Therefore, the Ecological Systems Theory proposed by Urie Bronfenbrenner will be employed to closely examine how the identities of Morrison’s characters are being shaped in the novel. The usage of the five systems on which Bronfenbrenner’s bioecological model is based– chronosystem, macrosystem, exosystem, mesosystem and microsystem, will provide an often missing holistic approach necessary for better understanding of how and why Morrison’s characters are (un)able to complete their developmental journey of identity construction successfully.